Chicken Egg Production in Aceh and Riau from 2009 to 2018 using Simple Linear Regression with SWOT Analysis Approach - Putra, Rizaldi; Tanjung, Amries Rusli; David, David; Renaldo, Nicholas; Cecilia, Cecilia (First Ciera Publisher, 2024)
This study aims to analyze the factors influencing fluctuations in chicken egg production and demand in Riau Province. The method of determining the area is determined purposively, namely intentionally by selecting in Indonesia. The data was analyzed using a simple linear regression method. In 2019, chicken egg production in Aceh Province was 1,804,721,455 and decreased by 2,462,278,545 in the previous year, namely 2018. In 2019, chicken egg production in Riau Province was 1,538,720,667 and decreased by 895,279,333 in the previous year, namely 2018. Chicken egg production in Riau Province was more stable than Aceh Province in 2018 to 2019. The study highlights the need for effective price stabilization mechanisms, enhanced supply chain efficiency, and improved feed cost management strategies. Future research can extend the study period to include more recent data for a better understanding of current trends.